A Door in Epynt/#/A Door in Epynt [[no pinyin available]]. - Dao, Bei (Xianggang guo ji shi ge zhi ye 2013., 2013)
Drawn from International Poetry Nights in Hong Kong 2013, A Door in Epynt is a chapbook of poetry by Menna Elfyn presented in Welsh, English, and Chinese. A Door in Epynt is also available, along with the chapbooks of other internationally renowned poets, in Islands or Continents (Eighteen-volume Set). Selected poems from this volume are featured in the anthology Islands or Continents: International Poetry Nights in Hong Kong 2013.